Best Practice Implementation of Digital Report Management Information System - Majidah Aqifah Mania; Mulyawan Safwandy Nugraha; Hamad Bin Khalifa (Lembaga Pendidikan Hikmatun Najah Blora, 2025)
This study aims to analyze the implementation of Madrasah Digital Report Card (RDM) at MA Al-Wathoniyah 5 in order to improve the efficiency and quality of education administration management. This research uses a descriptive qualitative method with data collection through documentation and interviews, which are analyzed using the Miles and Huberman technique, including data reduction, data presentation, and conclusion drawing. The results showed that RDM facilitates the management of grades, student attendance, and reporting in accordance with the Ministry of Religious Affairs standards. The automatic validation feature and account-based access control ensure data accuracy and security. Implementation constraints, such as limited budget and internet access, were overcome through a shared commitment between teachers, administrative staff and the foundation, as well as regular training and internal fundraising. The planned integration of RDM with other management systems, such as finance and student attendance, as well as the increased capacity of the local server, reflects the madrasah's vision to build a comprehensive and sustainable information system. In conclusion, RDM not only improves administrative efficiency but also becomes a relevant model of technological innovation in madrasah education.